2016
DOI: 10.1590/s1980-5764-2016dn1002003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Alzheimer's disease pathophysiology with PET

Abstract: Alzheimer's disease (AD) has been reconceptualised as a dynamic pathophysiological process characterized by preclinical, mild cognitive impairment (MCI), and dementia stages. Positron emission tomography (PET) associated with various molecular imaging agents reveals numerous aspects of dementia pathophysiology, such as brain amyloidosis, tau accumulation, neuroreceptor changes, metabolism abnormalities and neuroinflammation in dementia patients. In the context of a growing shift toward presymptomatic early dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 147 publications
(211 reference statements)
0
22
0
3
Order By: Relevance
“…Unfortunately, PiB does not label Aβ deposits in some mouse models, including both APP/PS1 and Tg2576 (Klunk et al, ; Snellman et al, ), but at least one quantitative comparison between amyloid PET and methoxy‐X04 labeling in different mouse lines has been performed (Brendel et al, ). The significance of the differential affinity of imaging probes for various forms of Aβ is still an active area of research (Schilling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, PiB does not label Aβ deposits in some mouse models, including both APP/PS1 and Tg2576 (Klunk et al, ; Snellman et al, ), but at least one quantitative comparison between amyloid PET and methoxy‐X04 labeling in different mouse lines has been performed (Brendel et al, ). The significance of the differential affinity of imaging probes for various forms of Aβ is still an active area of research (Schilling et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation indicated that an important dose-response effect reflects the association between amyloid burden and cognitive decline (Farrell et al, 2017), which suggests that the rate of accumulation is a better predictor of cognitive decline than a single threshold. Besides, it is known that cognitive decline is strongly associated with Tau deposition (Aschenbrenner et al, 2018;Braak et al, 2006;Schilling et al, 2016). Hence, further studies assessing longitudinal amyloid and tau deposition in SuperAgers may help elucidate this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…), making early diagnostic screening as well as routine monitoring by these tools difficult (Loane & Politis ; Schilling et al . ). Instead, biomarkers based on differential expression of DNA (Ziegler et al .…”
Section: Biomarkers For Ad and Pdmentioning
confidence: 97%